(untitled) (Italian Journal of Public Health, 2006)
Knowledge and technologies arising from the Human Genome Project promise in time to offer new opportunities for the treatment and prevention of disease. The enterprise of public health genomics aims to bridge the gap between advances in basic research and their responsible and effective implementation in clinical services and public health programmes. Public health genomics stresses the importance of understanding how genes and environment act together to influence health; avoiding genetic exceptionalism; appreciating the social and political context of genomic advances; and encouraging critical evaluation of proposed new tests and interventions. New international networks and collaborations are being established to develop public health genomics and further its aims.